Peer Supports Was Related To Improving The Nurse’s Self-Efficacy In Caring For Covid-19 Patients In Hospitals - Dadan Bardah; Setyowati Setyowati; Tuti Afriani; Hanny Handiyani; Sarvita Dewi (Poltekkes Kemenkes Surakarta, 2022)
Background: Nurses who fought against Covid-19 are generally under pressure, so they are prone to anxiety and stress. This problem certainly affects the nurses' self-efficacy in caring for Covid-19 patients. Therefore, it is necessary to have support from nurse managers and colleagues to overcome this problem. This study aims to identify the correlation between nurse managers and peer support with nurses' self-efficacy in caring for Covid-19 patients in hospitals Methods: This study uses a quantitative descriptive method with a cross-sectional approach. The number of samples was 167 nurses from the Covid-19 referral hospital in Cirebon with the accidental sampling technique. Data were analyzed using the Chi-square test and multiple logistic regression tests. Results: The results showed that there was a correlation between peer support and nurses' self-efficacy (p <0.001), and there was not a correlation between nurse manager support and nurses' efficacy in caring for Covid-19 patients in hospitals (p = 0.229). The most influential factors on nurses' self-efficacy were peer support (OR: 3.207) and gender (OR: 2.229). Conclusion: Peer support was related to increasing the nurse's efficacy in caring for Covid-19 in the hospital. The recommendation is the hospitals need to increase support for nurses by providing motivation, information, and counselling for individuals who need it. Therefore the emotional burden of nurses can be reduced, and self-efficacy becomes better in doing the job.